Synthesis of 4-functionalized pyrazoles via oxidative thio- or selenocyanation mediated by PhICl2 and NH4SCN/KSeCN - Wu, Jialiang; Shi, Haofeng; Li, Xuemin; He, Jiaxin; Zhang, Chen; Sun, Fengxia; Du, Yunfei (Beilstein Journal of Organic Chemistry, 2024)
A series of 4-thio/seleno-cyanated pyrazoles was conveniently synthesized from 4-unsubstituted pyrazoles using NH4SCN/KSeCN as thio/selenocyanogen sources and PhICl2 as the hypervalent iodine oxidant. This metal-free approach was postulated to involve the in situ generation of reactive thio/selenocyanogen chloride (Cl–SCN/SeCN) from the reaction of PhICl2 and NH4SCN/KSeCN, followed by an electrophilic thio/selenocyanation of the pyrazole skeleton.
Keywords: PhICl2; pyrazoles; selenocyanation; thiocyanation; thiocyanogen chloride